Synergistic effects of Lespedeza and artichoke extracts in the therapy of chronic kidney disease: mechanisms and perspectives - Z.O. Serebrovska; D.О. Tolstun; N.V. Sykalo; I.O. Farkhidinov; V. Kropyva; S.A. Myhovan; V.P. Chizhova; T.I. Kovtonyuk; I.A. Samots; B.M. Mankovsky (Počki)
Chronic kidney disease (CKD) is a major global health issue associated with oxidative stress, inflammation, and fibrosis. Traditional pharmacological approaches have limitations due to side effects and insufficient efficacy in the late stages of the disease. This study explores the potential of combining Lespedeza (Lespedeza spp.) and artichoke (Cynara scolymus) extracts in CKD treatment. The nephroprotective effect of Lespedeza extract is manifested in the reduction of albuminuria, nitrogen, and creatinine levels in urine. This is achieved through both direct antioxidant action, protecting membrane structures, DNA, and mitochondria, and indirect anti-inflammatory action, reducing NF-κB and inflammasome activity, as well as the release of pro-inflammatory cytokines and chemokines. The nephroprotective effect of artichoke extract is primarily attributed to the inhibition of the Wnt/β-catenin signaling pathway, which reduces fibrosis, and the suppression of pro-inflammatory cytokines (IL-1β, IL-2, IL-6, TNF-α, NF-κB, TGF-β1), preventing the progression of chronic inflammation in the kidneys. Additionally, artichoke extract inhibits angiotensin-converting enzyme, reducing renal hypertension and protecting kidney tissue from damage. The synergistic effect of Lespedeza and artichoke extracts may provide multifactorial nephron protection, minimizing inflammation and slowing fibrosis progression. A literature review confirms the promise of this approach and highlights the necessity of further preclinical and clinical studies to determine optimal dosing regimens for CKD therapy.